2018
DOI: 10.1038/s41598-018-22670-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative roles of clpA and clpB in the survival of S. Typhimurium under stress and virulence in poultry

Abstract: By assisting in the proteolysis, disaggregation and refolding of the aggregated proteins, Caseinolytic proteases (Clps) enhance the cellular survival under stress conditions. In the current study, comparative roles of two such Clps, ClpA (involved in proteolysis) and ClpB (involved in protein disaggregation and refolding) in the survival of Salmonella Typhimurium (S. Typhimurium) under different stresses and in virulence have been investigated. clpA and clpB gene deletion mutant strains (∆clpA and ∆clpB) of S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 81 publications
3
19
0
Order By: Relevance
“…Athar et al (2018) also certified that ClpB performs important functions during low-pH stress response. Many previous observations showed that ClpB contributes to the survival of bacteria during heat stress (Squires et al, 1991;Athar et al, 2018;Sangpuii et al, 2018). Our results showed (Figure 3B) that the activity of ClpB was relatively unaltered at 30-40 • C and decreased evidently at 25 and 45 • C. ATPase activity decreased by only 7% at 40 • C relative to the highest value (at 30 • C), which revealed that ClpB efficiently functioned during heat stress, but not during cold stress.…”
Section: Atpase Activitysupporting
confidence: 49%
See 4 more Smart Citations
“…Athar et al (2018) also certified that ClpB performs important functions during low-pH stress response. Many previous observations showed that ClpB contributes to the survival of bacteria during heat stress (Squires et al, 1991;Athar et al, 2018;Sangpuii et al, 2018). Our results showed (Figure 3B) that the activity of ClpB was relatively unaltered at 30-40 • C and decreased evidently at 25 and 45 • C. ATPase activity decreased by only 7% at 40 • C relative to the highest value (at 30 • C), which revealed that ClpB efficiently functioned during heat stress, but not during cold stress.…”
Section: Atpase Activitysupporting
confidence: 49%
“… Athar et al (2018) also certified that ClpB performs important functions during low-pH stress response. Many previous observations showed that ClpB contributes to the survival of bacteria during heat stress ( Squires et al, 1991 ; Athar et al, 2018 ; Sangpuii et al, 2018 ). Our results showed ( Figure 3B ) that the activity of ClpB was relatively unaltered at 30–40°C and decreased evidently at 25 and 45°C.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations